2015
DOI: 10.1103/physreve.91.062902
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a differential-difference integrable(2+1)-dimensional system

Abstract: A Kadomtsev-Petviashvili- (KP-) type equation appears in fluid mechanics, plasma physics, and gas dynamics. In this paper, we propose an integrable semidiscrete analog of a coupled (2+1)-dimensional system which is related to the KP equation and the Zakharov equation. N-soliton solutions of the discrete equation are presented. Some interesting examples of soliton resonance related to the two-soliton and three-soliton solutions are investigated. Numerical computations using the integrable semidiscrete equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 54 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…Starting from the discrete Kadomtsev-Petviashvili (KP) equation, or the so-called Hirota-Miwa (HW) equation [31,32] , Shi et al have derived discrete KdV equation and discrete potential mKdV equation, as well as their Lax pairs and multi-soliton solutions [33,34] . The authors have done a series of work in finding integrable discretizations of soliton equations such as the short pulse equation [35,36] , (2+1)-dimensional Zakharov equation [37] , the Camassa-Holm equation [38,39] and the Degasperis-Proceli equaiton [40] . Therefore, it is a natural but definitely not a trivial problem for us to construct an integrable discrete analogue of the mCH equation (1).…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the discrete Kadomtsev-Petviashvili (KP) equation, or the so-called Hirota-Miwa (HW) equation [31,32] , Shi et al have derived discrete KdV equation and discrete potential mKdV equation, as well as their Lax pairs and multi-soliton solutions [33,34] . The authors have done a series of work in finding integrable discretizations of soliton equations such as the short pulse equation [35,36] , (2+1)-dimensional Zakharov equation [37] , the Camassa-Holm equation [38,39] and the Degasperis-Proceli equaiton [40] . Therefore, it is a natural but definitely not a trivial problem for us to construct an integrable discrete analogue of the mCH equation (1).…”
Section: Introductionmentioning
confidence: 99%
“…(2.12) and (2.13)). Note that the generalized Toda hierarchy is different from, and apparently has no relation to, the discrete Yajima-Oikawa hierarchy recently studied in [11,13] (also see [12] for a (2 + 1)-dimensional version [23,32,33] of the discrete Yajima-Oikawa system).…”
Section: Discussionmentioning
confidence: 99%
“…This generalization provides a discrete analog of the generalization of the KdV hierarchy to a long wave-short wave interaction hierarchy, called the Yajima-Oikawa hierarchy [9,10], in the continuous case. A space discretization of the Yajima-Oikawa system was already proposed in the recent paper [11] (also see [12]) and its Lax pair as well as the next higher symmetry was presented in [13]. The first flow of the generalized Toda hierarchy proposed in this paper provides, in a special case, a new integrable discretization of the Yajima-Oikawa system, which is essentially different from the discrete Yajima-Oikawa system studied in [11,13] and has its own advantages; in particular, the discrete Yajima-Oikawa system in this paper possesses not only a Lax pair and an infinite number of conservation laws but also a simple Hamiltonian structure, so the higher flows of the hierarchy can easily be constructed.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Conditions (9) and taking k 4ζ1−2 → −k 4ζ1−3 , we can Figs. 4 The same as Figs. 3 except that ϕ(y) = 0.5 sin(0.66y).…”
Section: Hybrid Solutions Consisting Of the Soliton Breather And Lump Solutions For Eq (1)mentioning
confidence: 99%
“…Nonlinear evolution equations (NLEEs) have been used to describe the wave propagations in fluid mechanics, plasma physics and nonlinear optics [1][2][3][4][5][6][7]. Solitions have been found that their shapes and amplitudes unchanged during the propagations [8].…”
Section: Introductionmentioning
confidence: 99%